GENETIC DIVERSITY, MORPHOMETRIC CHARACTERISTICS, PARASITOLOGICAL ASSESSMENT, AND ENVIRONMENTAL EVALUATION OF SILVER CATFISH (Chrysichthys nigrodigitatus) IN IWOPIN LAGOON, OGUN STATE, NIGERIA - Adeleke, Mistura Temitope; Oladunjoye, Rasheed Yemi; Adekunle, Oladunni Nimota; Mogaji, Hammed .O.; Akinyoola, Omolara .I.; Lawal, Olusegun .A.; Aladejana, Abdulrahman A.; Siyanbola, Joy T. (Nigerian Journal of Fisheries, 2025)
Silver catfish (Chrysichthys nigrodigitatus) is a commercially important freshwater species in West Africa that is increasingly threatened by genetic erosion and parasitic infections in aquaculture and capture fisheries. This study assessed genetic diversity, morphometric variations, parasitological status, and environmental conditions in 76 silver catfish specimens collected from six sites in Iwopin Lagoon, Ogun State, Nigeria, between January and August 2025. Inter-Simple Sequence Repeat (ISSR) molecular analysis at five loci revealed exceptionally high genetic polymorphism with a mean allele number of 4.60 per locus, gene diversity (He) of 0.756, and polymorphism information content (PIC) of 0.715. Analysis of Molecular Variance (AMOVA) revealed FST = 0.225 (p < 0.05), indicating robust intra-population diversity suitable for selective breeding. Morphometric analysis demonstrated significant site-specific variation: mean total length 32.27cm, weight 308.97g. Length- weight regression exhibited positive allometric growth (Wt = 730.46 × TL32.21, R² = 0.464, p = 0.005). Parasitological examination revealed widespread parasitic infections: Cryptobia spp. (33%), Fasciola gigantica (26%), Entamoeba histolytica (14.5%), Hymenolepis diminuta (14.5%), Echinostoma cinetorchis (6%), and Brachylaima cribbii (6%). Mean parasite intensities ranged from 2.00 to 3.50 parasites per infected fish. Physicochemical parameters indicated good water quality. Neighbour-joining analysis identified two genetic clusters with minimal genetic distances (0.1–0.6), suggesting microhabitat-driven population structuring. These findings demonstrated that C. nigrodigitatus in Iwopin Lagoon maintains high adaptive potential and genetic fitness but requires targeted parasite management strategies and continued genetic monitoring to optimise aquaculture productivity and sustainability.